A comparative study of antivirus performance against android malware - Rosli, Nur Syaqirah Iwani; Buja, Alya Geogiana (College of Computing, Informatics, and Mathematics, 2025)
This study investigates the effectiveness of five antivirus programs (Kaspersky, AVG, McAfee, TrendMicro, and Bitdefender) on Android devices, focusing on key performance metrics such as detection rates, battery usage, storage management, and operating temperature. Employing a mixed-methods approach, the research combines qualitative and quantitative data to provide a comprehensive assessment of each antivirus program's capabilities. The findings reveal that Kaspersky and AVG excel in detection rates while maintaining efficient energy usage and low device temperatures. Conversely, McAfee exhibits higher power consumption and lower detection rates, and TrendMicro and Bitdefender, despite good detection capabilities, result in increased device temperatures. The study concludes that selecting antivirus software requires a balanced evaluation of protection efficacy and operational efficiency, highlighting the importance of diverse device testing and the integration of advanced performance assessment tools in future research.